Three new species of Daveyoungana Blocker & Webb (Hemiptera: Cicadellidae: Iassinae: Hyalojassini) from Brazil - Domahovski, Alexandre Cruz; Cavichioli, Rodney Ramiro (Zootaxa, 2019)
Three new species of Daveyoungana are described and illustrated from Brazil: Daveyoungana blockeri sp. nov. from Maranhão, Daveyoungana longibrachia sp. nov. from Rondônia and Daveyoungana pentacorni sp. nov. from Mato Grosso. A key to species of the genus is provided.